A Study on Determining Health Literacy and Neighborhood Perceptions Among Hospitalized Children and Their Parents in a City in Turkey - AVAN, Hakan; ARGIN, Vedat; VURAL, Birgül (Türkiye Sağlık Okuryazarlığı Dergisi, 2025)
Objective: This study investigates the relationship between health literacy and neighborhood perception among hospitalized children and their parents. Health literacy, encompassing the ability to understand and utilize health information, directly influences health outcomes. Health literacy levels are known to be low in Turkey. This study aims to assess the health literacy levels of children and parents, their perceptions of their neighborhoods, and the interaction between these variables.Materials and Methods: A cross-sectional study design was employed to evaluate health literacy and neighborhood perception among hospitalized children and their parents. The research was conducted between March 1 and October 30, 2024, at a University Health Practice and Research Hospital. Data collection instruments included the Child Demographic Information Form, the Health Literacy Scale for School-Aged Children, the Parent Demographic Information Form, the Health Literacy Scale, and the Perceived Neighborhood Disorder Scale.Results: A total of 648 individuals participated in the study, comprising 324 children and 324 parents. Among the parents, 33.3% were aged 31–39, while 36.5% of the children were aged 11–14. Sociodemographic comparisons revealed statistically significant differences in information access, evaluation, and application based on the number of children (p < 0.01).Conclusion: While the sociodemographic characteristics of parents, as well as the age, gender, and education level of children, were found to influence health literacy, no significant relationship was identified between health literacy and neighborhood perception. The findings highlight the importance of nurses taking active roles in initiatives aimed at improving health literacy.